2012
DOI: 10.3892/ol.2012.910
|View full text |Cite
|
Sign up to set email alerts
|

Leiomyoma of the gallbladder in a patient with metastatic gastrointestinal stromal tumor in the liver: A case report with differential diagnostic considerations

Abstract: Abstract. Mesenchymal tumor of the gallbladder is rare and the majority of cases present as sarcomas. Benign mesenchymal tumors of the gallbladder are extremely rare and to date, only one case of leiomyoma has been reported. In this report, we describe a second case of leiomyoma of the gallbladder, and discuss the differential diagnostic considerations. A 55-year-old female with metastatic gastrointestinal stromal tumors (GISTs) in the liver was identified to possess a tumorous lesion of the gallbladder. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
(6 reference statements)
2
0
0
Order By: Relevance
“…Leiomyoma of the gallbladder has been previously reported in one dog, 10 and a few case reports have been published in humans. 22,23,24 Gallbladder lymphoma was found in one dog in our study, and has been reported in single case reports in the dog 25 and cat. 26 This has also been a reported gallbladder neoplasm in humans.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Leiomyoma of the gallbladder has been previously reported in one dog, 10 and a few case reports have been published in humans. 22,23,24 Gallbladder lymphoma was found in one dog in our study, and has been reported in single case reports in the dog 25 and cat. 26 This has also been a reported gallbladder neoplasm in humans.…”
Section: Discussionsupporting
confidence: 77%
“…Leiomyoma was the next most common primary gallbladder neoplasm in our study, constituting three of the 15 (20%) cases. Leiomyoma of the gallbladder has been previously reported in one dog, 10 and a few case reports have been published in humans 22,23,24 . Gallbladder lymphoma was found in one dog in our study, and has been reported in single case reports in the dog 25 and cat 26 .…”
Section: Discussionsupporting
confidence: 65%